In-House Development of Data Collection and Signal Processing Applications for Vibration-Based Condition Monitoring. (July 2015) - Asnaashari, Erfan; Sinha, Jyoti K.; Andrew, Ian; Elbhbah, Keri; Hahn, W.
A simplified summary of in-house developed user friendly multi-channel data collection and signal processing capabilities for the vibration-based condition monitoring of plant assets in a cheaper manner is presented here.